Анализа укорељености серумског интестиналног протеина за везивање масних киселина, Д-млечне киселине и интерцелуларног фактора адхезије-1 код пацијената са сепсом и интестиналном исхемијом: Серумска интестинална протеинска везивања масних киселина, Д-млечна киселина и интерцелуларни фактор адхезије-1 код интестиналне исхемије са сепсом - Shu, Yujie; Lao, Bo; Song, Zhangzhang; Zhuang, Zhixing; Li, Hongzhang (Journal of Medical Biochemistry, 2025)
Objective: To analyze the correlations between the levels of serum intestinal fatty acid binding protein (I-FABP), D-lactic acid (D-Lac), and intercellular adhesion factor-1 (ICAM-1) in patients with sepsis complicated with intestinal ischemia‒reperfusion injury and the degree of intestinal mucosal injury and patient prognosis.Methods: A total of 236 patients with sepsis complicated with intestinal ischemia‒reperfusion injury were included in the reperfusion injury group, and 176 patients with sepsis alone during the same period were included in the sepsis group. Based on the extent of intestinal mucosal damage, individuals in the reperfusion injury group were split into three groups: mild injury (52 patients), moderate injury (116 patients), and severe injury (68 patients). The patients were further divided into a good prognosis group (188 patients) and a poor prognosis group (48 patients). The general clinical data of all patients and laboratory test indicators before and after treatment were collected and grouped for comparison. Correlation analysis was conducted via Spearman correlation analysis. Predictive value assessment was conducted via receiver operating characteristic (ROC) curves.Results: The reperfusion damage group had higher levels of I-FABP, D-Lac, ICAM-1, and IMA than the sepsis alone group, whereas the GLP-1 level was lower (P
Keywords: Ишемија црева са сепсом; Серумска интестинална протеин за везивање масних киселина; D-mlječna kiselina; Интерцелуларни фактор адхезије-1; Прогностичка корелација